#### Answer

$p+11$

#### Work Step by Step

The distributive property holds that $a(b+c)=ab+ac$ (for real numbers $a$, $b$, and $c$).
Therefore, $-6p+5-4p+6+11p=(-6-4+11)p+(5+6)=(1)p+(11)=p+11$.

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

$p+11$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.